Metabolism of plant polysaccharides by Leucoagaricus gongylophorus, the symbiotic fungus of the leaf-cutting ant Atta sexdens L. - Gomes De Siqueira, Célia [UNESP] (1998)
Atta sexdens L. ants feed on the fungus they cultivate on cut leaves inside their nests. The fungus, Leucoagaricus gongylophorus, metabolizes plant polysaccharides, such as xylan, starch, pectin, and cellulose, mediating assimilation of these compounds by the ants. This metabolic integration may be an important part of the ant-fungus symbiosis, and it involves primarily xylan and starch, both of which support rapid fungal growth. Cellulose seems to be less important for symbiont nutrition, since it is poorly degraded and assimilated by the fungus. Pectin is rapidly degraded but slowly assimilated by L. gongylophorus, and its degradation may occur so that the fungus can more easily access other polysaccharides in the leaves.